2019
DOI: 10.1055/s-0039-1693272
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Imaging, and Endoscopic Profile of Patients with Abdominal Tuberculosis

Abstract: AimsThe aim is to study the clinical, imaging, and endoscopic profile of patients with abdominal tuberculosis (TB) in a tertiary care center. Subjects and Methods This was a prospective observational study conducted at Meenakshi Medical College Hospital, Kancheepuram, over a 3-year period, from March 2011 to February 2014. A total of 76 patients were diagnosed with abdominal TB based on their clinical, pathological, endoscopic, and radiological features. A meticulous history and physical examination with compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In the study "clinical, imaging, and endoscopic profile of patients with abdominal tuberculosis" by Shafiq et al, 1 the author has reported a single center experience of 76 cases of abdominal tuberculosis over the study period of 3 years. This is consistent with the statistics that India has the world's largest number of tuberculosis cases which is around 26% of the world TB cases, followed by China and South Africa.…”
Section: The Diagnostic Conundrum Of Crohn's Disease and Intestinal Tbmentioning
confidence: 99%
“…In the study "clinical, imaging, and endoscopic profile of patients with abdominal tuberculosis" by Shafiq et al, 1 the author has reported a single center experience of 76 cases of abdominal tuberculosis over the study period of 3 years. This is consistent with the statistics that India has the world's largest number of tuberculosis cases which is around 26% of the world TB cases, followed by China and South Africa.…”
Section: The Diagnostic Conundrum Of Crohn's Disease and Intestinal Tbmentioning
confidence: 99%